Comportamento autonômico cardíaco dos aeronavegantes da Força Aérea Brasileira em hipóxia hipobárica e sua relação com o tempo de aparecimentos dos sintomas de hipóxia e a aptidão física - Honorato, Fernando Sousa (2021)
Background: The occurrence of hypobaric hypoxia (HH) during the flight can cause incidents and / or accidents and result in death. HH induces changes in cardiac autonomic function that can be assessed by heart rate variability (HRV). However, the hypothesis that heart rate variability is an instrument for prognostic / confirmatory assessment of self-reported assessment of hypoxia symptoms remains to be studied. It is known that the level of physical fitness can contribute to efficient autonomous modulation. However, no study has examined the association between fitness, HRV and symptoms of HH in Brazilian Air Force (FAB) aircraft. Objective: Analyze the influence of hypobaric hypoxia on cardiac autonomic function during the time of onset of the first symptoms (TAS) and its association with physical fitness in Brazilian Air Force airmen. Methods: Male airmen, trained and belonging to the staff of the Brazilian Air Force (n = 23; 30 + 6.7 years) were subjected to flight simulation in a 25,000 ft hypobaric chamber. Heart rate variability was recorded with a Polar® cardiac monitor. The data were analyzed at the time-domain and nonlinear domain using the Kubios software. We evaluated pulse oximetry with the Mindray PM-60 oximeter. The documentary analysis of the results achieved by the airmen in the physical fitness assessment test (TACF) related to anthropometric assessment and body composition, cardiorespiratory fitness and neuromuscular tests was performed. Results: The comparison between the moments of rest vs. hypoxia reveals that the values of the iRR, RMSSD, NN50, SD1 indices decreased, and the mean heart rate and SD-HR index values increased (p <0.05). The individual analysis of hypoxia-rest variation showed that 100% of the aircraft had a negative delta for the iRR, average HR and RMSSD indices. The time of onset of hypoxia symptoms was not associated with the variables of body composition, physical fitness, and oxygen saturation or with HRV indices. The visual inspection of the graphics of the iRR shown a decrease in the length, breadth, and loss of linearity during the hypoxia (p <0.05) in all aircraft. Conclusion: HH decreases the HRV index before TAS, thus demonstrating that cardiac autonomic modulation seems to be more sensitive to the effects of HH at 25,000ft than the self-reported subjective perception of symptoms. Thus, mobile devices in order to alert the pilot in advance of a hypoxia can be created allowing more time for his action to reestablish control of flight. There was no association between the TACF indexes and the TAS. Keywords: hypoxia, hypobaric, sympathetic, parasympathetic, frequency variability, physical fitness assessment test, oximetry